ANALISIS PENGARUH CORPORATE SOCIAL RESPOSIBILITY (CSR) PERUSAHAAN (DIVERSITY, EMPLOYEE SUPPORT, DAN ENVIROMENT) TERHADAP KINERJA KARYAWAN (STUDI PADA PT. AQUA GOLDEN MISISIPI CITEUREUP) - Indrawan, Ruli; Bidayati, Utik (Jurnal Fokus Manajemen Bisnis, 2017)
The purpose of this study was to determine the effect of Corporate Social Responsibility (CSR) of the Company (Diversity, Employee Support, and Environment) on Employee Performance at PT. Aqua Golden Misisipi Citeureup either partially (individually) or simultaneously (together). The population in this study amounted to 767 employees and then taken as many as 90 samples using purposive sampling technique sampling. The type of data is primary data and data collection using a questionnaire that has been tested for validity using confirmatory factor analysis (CVA), and reliability testing using Alpha Crobach, analysis techniques using Multiple Regression. Based on the analysis with statistical tools SPSS V 20 it can be concluded that the employee support variable (X2) partially influences employee performance (Y) while the diversity variable (X1) and environment (X3) partially does not significantly influence employee performance (Y ). While simultaneously (together) diversity (X1), employee support (X2) and environment (X3) significantly influence employee performance (Y) at PT. Aqua Golden Misisipi Citeureup.